EDUCATION ON THE MANAGEMENT AND EFFICIENCY OF ELECTRICAL ENERGY USE FOR HOUSEHOLDS IN KAMPUNG TAMBAK ASRI MOROKREMBANGAN SURABAYA - Anshory, Izza; Abror, M. (Journal of Social Comunity Services, 2025)
Objective: The use of electrical energy by housewives is often less efficient due to their habit of leaving appliances connected and low awareness of managing energy. This has an impact on increasing electricity costs to be paid and energy waste. This community service activity aims to increase the understanding of housewives in the correct and efficient use of electrical energy. Method: The activity was held at the Tambak Asri 204 Al Islam Mosque in Surabaya which was attended by 35 housewives who were members of the Ta'lim At-Taubah Assembly. The method of implementing service includes making and distributing energy-saving educational posters, interactive counseling on electricity use habits, and energy-efficient household appliances simulations. Results: The results of the activity showed an increase in participants' knowledge about the importance of unplugging electrical equipment after use, turning off lights when not in use, and choosing energy-saving electrical devices such as Light Emitting Diode (LED) lamps. Novelty: Thus, this activity is able to foster collective awareness in reducing electricity waste while supporting household cost savings and environmental sustainability.